The risk of stanford type-A aortic dissection with different tear size and location: a numerical study. Issue 2 (December 2016) - Shi, Yue; Zhu, Minjia; Chang, Yu; Qiao, Huanyu; Liu, Yongmin
Abstract Background This study is to investigate the influence of hemodynamics on Stanford type-A aortic dissection with different tear size and location, to provide some support for the relationships between the risks (rupture, reverse tearing and further tearing) and tear size and location for clinical treatment. Methods Four numerical models of Stanford type-A aortic dissection were established, with different size and location of the tears. The ratio of the area between the entry and re-entry tears(RA) is various within the model; while, the size and the location of the re-entry in the distal descending aorta are fixed. In model A11 and A21, the entry tears are located near the ascending aorta. The RA in these models are 1 and 2, respectively; In the model B11 and B21, the entry tears are located near the proximal descending aorta and the RA in these models are again assigned to 1 and 2, respectively. Then hemodynamics in these models was solved with numerically and the flow patterns and loading distributions were investigated. Results The flow velocity of the true lumen in model A21, B21 is lower than that in A11, B11, respectively; the time-averaged wall shear stress (TAWSS) of the false lumen in model A21 and B21 is higher, and for ascending aorta false lumen, A11, A21 are higher than B11, B21, respectively. False lumen intimal wall pressure of A11, A21 are always higher than the true lumen ones. Conclusion The variation of the RA can significantly affect the dynamics of blood within the aortic dissection. When the entry tear size is larger than the re-entry tear ones, the false lumen, proximal descending aorta and the wall near re-entry tear are prone to cracking. Entry tear location can significantly alter the hemodynamics of aortic dissection as well. When entry tear location is closer to proximal ascending aorta, false lumen continues to expand and compress the true lumen resulting in the true lumen reduction. For proximal ascending aorta, high pressure in false lumen predicts a higher risk of reverse tear.